2008
DOI: 10.1101/lm.773208
|View full text |Cite
|
Sign up to set email alerts
|

Conditional forebrain deletion of the L-type calcium channel CaV1.2 disrupts remote spatial memories in mice

Abstract: To determine whether L-type voltage-gated calcium channels (L-VGCCs) are required for remote memory consolidation, we generated conditional knockout mice in which the L-VGCC isoform Ca V 1.2 was postnatally deleted in the hippocampus and cortex. In the Morris water maze, both Ca V 1.2 conditional knockout mice (Ca V 1.2 cKO ) and control littermates displayed a marked decrease in escape latencies and performed equally well on probe trials administered during training. In distinct contrast to their performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
102
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 29 publications
7
102
0
2
Order By: Relevance
“…The conditional deletion of Ca v 1.2 in the neocortex and hippocampus of Ca v 1.2 cKO mice, two brain regions critically involved in fear conditioning and its extinction (Maren 2001;Myers and Davis 2006), has previously been described (White et al 2008). We have subsequently conducted a series of experiments to examine the expression pattern of cre-recombinase and to determine the extent of the deletion of Ca v 1.2 in the basolateral amygdaloid complex (BLA; composed of the lateral, basolateral, and basomedial amygdaloid nuclei).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conditional deletion of Ca v 1.2 in the neocortex and hippocampus of Ca v 1.2 cKO mice, two brain regions critically involved in fear conditioning and its extinction (Maren 2001;Myers and Davis 2006), has previously been described (White et al 2008). We have subsequently conducted a series of experiments to examine the expression pattern of cre-recombinase and to determine the extent of the deletion of Ca v 1.2 in the basolateral amygdaloid complex (BLA; composed of the lateral, basolateral, and basomedial amygdaloid nuclei).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously demonstrated that these mice have disrupted remote spatial memories (White et al 2008). Here we demonstrate that conditional deletion of Ca v 1.2 does not disrupt consolidation of conditioned fear.…”
mentioning
confidence: 99%
“…The voltagegated L-type calcium channel is formed from the multimerization of the pore-forming α 1c subunit (encoded by CACNA1C), which directly interacts with the intracellular β 2 subunit (encoded by CACNB2), and a third extracellular membrane anchored α 2 δ subunit (71, 72). Calcium channels have been extensively studied in neuroscience and are critically important for learning, memory, and synaptic plasticity (73)(74)(75). Several Mendelian disorders result from deleterious mutations in calcium channel subunits.…”
Section: Genomic Results For Schizophreniamentioning
confidence: 99%
“…Hippocampal function depends mainly on Ca V 1.2. This isoform is required for hippocampal spatial memory formation (Moosmang et al, 2005a;White et al, 2008) for protein synthesisdependent, NMDA receptor-independent late-phase long-term potentiation (LTP) in CA3-CA1 synapses, and for activation of the microtubule-associate protein kinase/cAMP/calcium response element binding protein (CREB) signaling cascade (Moosmang et al, 2005a). In contrast with Ca V 1.2, Ca V 1.3 does not contribute to CA3-CA1 hippocampal LTP and the spatial memory encoding in the Morris water maze appeared normal in Ca V 1.3-deficient mice (McKinney and Murphy, 2006).…”
Section: Ca V 1 Channel Familymentioning
confidence: 99%